[Retracted Article] Autecology of An Endemic Palm Pinanga arinasae J.R.Witono in Bali, Indonesia - Rajif Iryadi; Sutomo Sutomo (Journal of Tropical Biodiversity and Biotechnology, 2020)
Nyabah, or Jabah (Pinanga arinasae J.R.Witono) is pinanga or palm which is endemic to Bali.  This study aimed to determine the distribution, abundance patterns, and habitat preferences of P. arinasae, and also its natural microclimate on Mount Pengelengan, Bali, on which the species occurred. Field observations were conducted using systematic sampling method. 20 x 20 m plots were made along a transect of forest path on the right and the left, with 100 m distance between plots. Results showed P. arinasae distribution in Mount Pengelengan grows clumped with different abundance in each plot. Microclimate observations (light intensity, humidity relative, and air temperature) each plot varies the effect on the distribution and abundance of P. arinasae. Light intensity is the main factor that regulates the abundance and distribution of P. arinasae and this species has the most abundant on the limited canopy cover area which has high the light intensity at 1319 lux. Autecological data is the first step in conservation efforts.Retraction Note. On 16 October 2020, the editorial team were made aware that similar dataset of this article had been published in Chapter III “Vegetation Ecology of Bedugul” page 29-53 of a book titled “Ecology of Bedugul Basin Bali” (ISBN: 978-979-8275-55-5), published by Seameo Biotrop in 2018. An investigation was held and side-by-side comparison showed that this article has 35.6% similarity with the book chapter including the data tables and several paragraphs of text. It is clear this article is a duplicate publication which is categorized as publication misconduct. Hence, this article is retracted and the authors are notified.